Identifying the immunomodulatory components of helminths. (June 2015) - Shepherd, C.; Navarro, S.; Wangchuk, P.; Wilson, D.; Daly, N. L.; Loukas, A.; La Flamme, Anne Camille
Summary Immunomodulatory components of helminths offer great promise as an entirely new class of biologics for the treatment of inflammatory diseases. Here, we discuss the emerging themes in helminth‐driven immunomodulation in the context of therapeutic drug discovery. We broadly define the approaches that are currently applied by researchers to identify these helminth molecules, highlighting key areas of potential exploitation that have been mostly neglected thus far, notably small molecules. Finally, we propose that the investigation of immunomodulatory compounds will enable the translation of current and future research efforts into potential treatments for autoimmune and allergic diseases, while at the same time yielding new insights into the molecular interface of host–parasite biology.